Analysis of An SEIQRVS Epidemic Model for Corona Virus Infectious Disease - et. al., Smriti Agrawal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, a SEIQRVS epidemic infectious disease model is proposed and can simulate the process of COVID-19. The effect of the corona virus on infected individuals is shown. It is a well-known concept that the circulation of infectious diseases may be the reason of growing virus in the susceptible population. The increase in the death rate of the virus is one of the strategies to control infectious diseases. The proposed model system shall be explored to explain the growth and death rate of the virus in the susceptible population. It is shown that the model exhibits two equilibria, namely, the disease-free equilibrium and the endemic equilibrium. The global dynamics are completely determined by the basic reproduction number. If the basic reproduction number is less than 1, the disease-free equilibrium is globally stable which leads to the eradication of the disease from the population. If the basic reproduction number is greater than one, an endemic equilibrium exists and is globally stable in the feasible region under certain conditions. Finally, taking biologically relevant parametric values, numerical simulations are performed to illustrate and verify the analytical results. Normalized forward sensitivity indices are calculated for effective reproduction number, and state variables at endemic equilibrium on various parameters and respective sensitive parameters are identified.